Numerical methods in thermal problems - Lewis, R. W. (Roland Wynne); Cross, J. T.; International Conference for Numerical Methods in Thermal Problems (10th : 1997 : Swansea, UK) (Swansea, UK : Pineridge Press, 1997)
40